Knowledge, Attitude and Practice of Dentists Regarding Cross Infection in Dental Teaching Hospitals of Peshawar - Nadia Qazi; Syed Nasir Shah (Journal of Gandhara Medical and Dental Sciences, 2016)
OBJECTIVES: The objective of the current study was to assess knowledge, attitude and practices of dentist regarding cross infection in Khyber College of Dentistry (KCD) and Sardar Begum Dental College (SBDC) Peshawar. MATERIALS AND METHODS: This descriptive cross sectional study was conducted at two tertiary care hospitals having sample size 214 with 94 males and 121 females. A pilot study was conducted at Hayatabad Medical Complex to assess the reliability of questionnaire. Self administered anonymous questionnaire was administered to 214 dentists. The dentist in each health care facility was observed for their knowledge, attitude and practice regarding cross infection. RESULTS: Knowledge of dentist’s was optimum but they were lacking sufficient knowledge in areas of sterilization and cross infection due to waste material present in pipes of dental units. Significant numbers of them 28.8% were not agreed with the role of wearing rings in cross infection during dental procedure. Although lack of hand washing and impression was considered as a source of cross infection and 33.9% reported poor attitude regarding hand washing, 39.9% were not regarding the hygiene of nails in cross infection control. Similarly only 59% of them have shown positive attitude towards the vaccination of dental professionals. Although the knowledge and attitude was seen acceptable but their practices regarding the infection control were lacking in area of use of N95 respirator, taking off jewelry during dental surgeries, use of filtered water, use of anti-retraction valve, use of rubber dam for aerosols, use of separate box for sharp disposal and use of disinfectants in dental units.. CONCLUSION: From current study it was concluded that dentists have good knowledge but poor practice regarding various aspect of infection control which provide an indication either lack of availability facilities or poor supervision and monitoring, due to lack of policy and implementation regarding cross infection control in dental units